Penerapan Model Pembelajaran Berdiferensiasi Pada Pelajaran Matematika Kelas 1 Di SDN Kebon Jeruk 06 Jakarta - Herawati, Ety; Priyanti, Nita; Kasih, Delina (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to describe the application of the differentiated learning model in mathematics subjects in class 1 of SDN Kebon Jeruk 06. Differentiated learning is a teaching approach that is tailored to students' needs, interests and level of learning readiness. This model includes three main aspects, namely differentiation of content, processes and learning products. This research uses a qualitative descriptive method, with data collection through observation, interviews and documentation studies. The research subjects consisted of grade 1 teachers at SDN Kebon Jeruk 06 as learning implementers. The collected data was analyzed using an interactive approach which included data reduction, data presentation, and drawing conclusions. results of the research show that the application of differentiated learning in grade 1 mathematics subjects is carried out through adjusting lesson materials according to students' abilities, providing various assignments to accommodate differences in learning processes, as well as variations in learning products produced by students. Teachers play an active role in designing and implementing adequate learning strategies to ensure that each student can achieve learning goals according to their respective abilities. From this research it can be concluded that differentiated learning has a positive impact on student motivation and learning outcomes in mathematics lessons. However, its implementation requires careful planning and adequate support from the school.